Chapter 9 "Nonsense Rides Piggyback on Sensible Things" The Past, Present, and Future of Graphology - Thorpe, Deborah Ellen (Springer Nature, 2018)
"Nonsense rides piggyback on sensible things", declares professional sceptic and questioned-document analyst Joe Nickell concerning graphology. This chapter examines graphology's enduring allure and reach, despite its controversies, and considers its relationship with other types of handwriting analysis. It first asks: is it possible to metaphorically "dissect" the page of handwritten texts, to scrutinize writing as a "medical paratext" rich in information about the writer's state of health? It then interrogates the nature of the connection between physical and mental states and handwriting. It demonstrates how academics are going "back to basics" with their enquiries into individual difference and handwriting features, and how digital methodologies are contributing to this. Thus, this chapter is an updated study of graphology, providing a wider understanding of the concept of the paratext by considering the information captured in handwriting in the context of a digital age.